2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5685228
|View full text |Cite
|
Sign up to set email alerts
|

Defending Resource Depletion Attacks on Implantable Medical Devices

Abstract: Implantable Medical Devices (IMDs) have been widely used to treat chronic diseases such as cardiac arrhythmia and diabetes. Many IMDs are enabled with wireless communication capabilities and can communicate with an outside programmer/reader wirelessly. With the rapid growth of IMDs, IMD security becomes a critical issue since attacks on IMDs may directly harm the patient. Typical IMDs have very limited resource in terms of energy, computation and storage. In this research, we identify a new kind of attacks on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 14 publications
0
63
0
Order By: Relevance
“…To reduce battery consumption in IMDs, methods have been suggested that use an external device (called a cloaker) [17][18][19]. A cloaker is a device, such as a smartphone, that operates on behalf of the IMD.…”
Section: Communication Cloakingmentioning
confidence: 99%
“…To reduce battery consumption in IMDs, methods have been suggested that use an external device (called a cloaker) [17][18][19]. A cloaker is a device, such as a smartphone, that operates on behalf of the IMD.…”
Section: Communication Cloakingmentioning
confidence: 99%
“…The attacker can predict the value of Hamming weight ℎ of in time for each acquired traces . Equation (2) can compute the PCC between these predictions of Hamming weight ℎ and the instantaneous power consumption of the set of acquired traces . The maximum PCC corresponds to the correct key.…”
Section: The Correlation Power Analysismentioning
confidence: 99%
“…With the development of information technology, information security plays an important role in medical system [1,2], communications [3], finance [4], and other fields. Sidechannel analysis [5,6] which focuses on exploiting the implementation or some measurable nonmathematical property of a cryptographic system, was introduced by Kocher et al in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Hei et al showed a simple yet effective attack where adversaries force the IMD to respond to their messages, which reduces the battery life of the IMD [13]. Halperin et al analysed the proprietary protocol between the device programmer and a second generation ICD to communicate over the short-range communication channel [12].…”
Section: Software Radio-based Attacks On Imdsmentioning
confidence: 99%